Isolation and Toxicity Test of Chitosan from Green Mussels (Perna viridis L.) With Brine Shrimp Lethality Test (BSLT) Method - Ridwanto Ridwanto; Audry Pratiwi; Zulmai Rani (Jurnal Sains dan Kesehatan, 2023)
Green Mussels (Perna viridis L.) is one of Indonesia's fishery resources. The purpose of this study was to determine the toxicity level of chitosan from green clam shells (Perna viridis L.) by looking at the LC50 value tested on the BSLT method. This study included isolation of chitin and chitosan: deproteination, demineralization, depigmentation and deacetylation of chitin into chitosan, chitosan characterization, FTIR, and chitosan Toxicity Test using the BSLT method to see the number of deaths of Artemia salina L larvae obtained data (LC50). The results showed that the Chitosan Green Clam Shell (Perna viridis L.) had an LC50 of 4369.1806 ?g/mL. The results showed that green clam shell chitosan (Perna viridis L.) was non-toxic (LC50 > 1000 ?g/mL) in the BSLT test. Keywords:          BSLT, Chitosan, Shellfish, Toxicity Test